Physical habitat and water chemistry changes induced by logging and gold mining in French Guiana streams - Dedieu N.; Allard L.; Vigouroux R.; Brosse S.; Céréghino R. (Knowledge and Management of Aquatic Ecosystems, 2014)
Understanding the effects of disturbances on the physical-chemical quality of ecosystems is a crucial step to the development of ecosystem assessment tools. 95 sampling sites distributed among 4 categories of disturbance, i.e.: reference, logging, formerly and currently gold mining, were characterized using stream physical and chemical variables. Our hypotheses were: (i) logging and gold mining activities primarily affect the physical habitat structure of streams and (ii) both have an effect on chemical environments through nutrient and/or fine particulate resuspension. We demonstrate that physical variables describing the river bottom, and suspended solids discriminate both current and formerly gold mined sites from reference sites, while, whatever the type of impact encountered, nutrient concentrations do not prove relevant to measure human impacts. To understand distribution patterns of aquatic organism across FG, future research should thus aim at examining the match between physical-chemical and biological classifications of small streams under reference and impacted conditions.